Iraq : First and Second Reviews Under the Stand-By Arrangement, Financing Assurances Review, and Request for Waiver of Nonobservance and Applicability of Performance Criteria-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report ;, 2006)
The government of Iraq is committed to reform the pension law before it goes into effect. Good progress has been made in setting up a payments system. The Central Bank of Iraq (CBI) and ministry of finance are coordinating their strategy toward restructuring the state-owned banks. The government expects to initiate negotiations on resolving non-Paris Club official claims very soon. Iraq's medium-term economic prospects look reasonably favorable, but are subject to considerable risk. The new government has taken important and decisive measures to bring the program back on track.